Peningkatan Kesadaran Masyarakat terhadap Metode Pengolahan Sampah di Dusun Klaci 1 Margoluwih Sayegan Sleman: Increasing Public Awareness about Waste Treatment Methods in Klaci 1 Margoluwih Sayegan Sleman Village - Lesmana, Surya Budi; Faizah, Restu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Waste has become a problem for all of us and the environment in which we live. Every day, garbage is produced as a result of various human activities. Natural waste production is increasing in lockstep with population and industry growth but has yet to be proportional to final landfill capacity. This causes issues with waste management. This service aims to increase public awareness of waste management methods and processing waste on a household scale. This service uses the socialization of waste sorting and training in processing organic waste from households. This service uses the socialization of waste sorting and training in processing organic waste from households. This service program benefits the community in the following ways: the community is aware of the various types of waste that exist, the community has increased waste management awareness, and the community is aware of proper waste management and processing.